Human Capital Efficiency and Firm Value: Empirical Evidence on Companies Listed on the Indonesia Stock Exchange - Leni Hartati; RR. Ella Evrita H (International Journal of Management Science and Information Technology, 2026)
The development of a knowledge-based economy positions human capital as a strategic asset capable of creating sustainable competitive advantage and increasing firm value. In public companies, efficient human capital management is increasingly important because it influences not only operational performance but also investor perceptions in the capital market. This study aims to analyze the effect of Human Capital Efficiency (HCE) on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study employs a quantitative approach with a causal research design using panel data obtained from annual financial reports of manufacturing firms listed on the IDX during the 2020–2024 period. The sample was selected using purposive sampling criteria, resulting in 60 companies with 300 observations. Human Capital Efficiency is measured using the Value-Added Intellectual Coefficient (VAIC™) approach, while firm value is measured using Tobin’s Q. Panel data regression analysis is conducted with control variables including firm size, leverage, and profitability. The results reveal that Human Capital Efficiency has a positive and significant effect on firm value, indicating that companies capable of efficiently managing human resources tend to achieve higher market valuation. In addition, firm size and profitability positively influence firm value, whereas leverage has a negative effect. These findings suggest that efficient human capital management enhances investor confidence, organizational productivity, and long-term corporate competitiveness. Theoretically, this study strengthens Human Capital Theory and the Resource-Based View by providing empirical evidence from the Indonesian manufacturing sector. Practically, the findings imply that manufacturing firms should prioritize strategic human resource investments, employee capability development, training programs, and talent retention strategies to improve firm value and sustain competitive advantage.